IMCSA: Providing Better Sequence Alignment Space for Industrial Control Protocol Reverse Engineering. (24th November 2022) - Ji, Yukai; Huang, Tao; Ma, Chunlai; Hu, Chao; Wang, Zhanfeng; Fu, Anmin
Abstract : Nowadays, with the wide application of industrial control facilities, industrial control protocol reverse engineering has significant security implications. The reverse method of industrial protocol based on sequence alignment is the current mainstream method because of its high accuracy. However, this method will incur a huge time overhead due to unnecessary alignments during the sequence alignment process. In this paper, we optimize the traditional sequence alignment method by combining the characteristics of industrial control protocols. We improve the frequent sequence mining algorithm, Apriori, to propose a more efficient Bag-of-Words generation algorithm for finding keywords. Then, we precluster the messages based on the generated Bag-of-Words to improve the similarity of the message within a cluster. Finally, we propose an industrial control protocol message preclustering model for sequence alignment, namely, IMCSA. We evaluate it over five industrial control protocols, and the results show that IMCSA can generate clusters with higher message similarity, which will greatly reduce the invalid alignments existing in the sequence alignment stage and ultimately improve the overall efficiency.